Konjungtivitis dan COVID-19 - Rifqi Fadhil Maulana; Nanda Cynthia Huzna; Rani Himayani (Medula, 2023)
The coronavirus disease 2019 (COVID-19) pandemic started as an outbreak in Wuhan and has since spread worldwide. To date, the exact transmission route of COVID-19 is still unclear. The respiratory tract may not be the only route of transmission of this virus. Some studies have hypothesized that COVID-19 droplets, or contaminated hands, may also contaminate the conjunctiva and serve as an initial site of infection. Conjunctivitis, a common disease caused by either bacteria or viruses, has previously been described in association with coronavirus infections in some studies. Further reports suggest that when no eye protection is used, the virus can also be transmitted through aerosol contact with the conjunctiva and cause infection. However, the possibility of SARS-CoV-2 transmission through the conjunctiva is still controversial. Despite some controversy about whether the conjunctiva functions as an important route for SARS-CoV-2 infection, there is accurate evidence that the conjunctiva plays a role as an entry point and reservoir for the virus. Additionally, there is a possibility that unknown receptors in the conjunctiva may be involved in SARS-CoV-2 infection. The level of viral replication in the conjunctiva is still unknown and is another factor that can describe the impact of the eye in the pathogenesis. Studies have shown that SARS-CoV-2 viral RNA is more likely to be found in the ocular secretions of COVID-19 patients who have conjunctivitis symptoms, although it has also been found in patients without eye disorders in some cases. This literature review discusses the relationship between SARS-CoV-2 and conjunctivitis.